Factors associated with worsened clinical symptoms of psoriasis and disease-related quality of life during the COVID-19 lockdown: A cross-sectional study - Burkauskas, Julius; Slabadiene, Margarita; Podlipskyte, Aurelija; Steibliene, Vesta (Frontiers in Medicine, 2023)
Objective In this cross-sectional study, we aimed to evaluate the factors associated with psoriasis symptom worsening and impaired quality of life (QoL) in individuals with psoriasis during the COVID-19 pandemic lockdown. Methods During the second COVID-19 national lockdown (January–April 2021) in Lithuania, individuals diagnosed with psoriasis were invited to fill in an anonymous online survey including sociodemographic and life-style factors, psoriasis-related clinical symptoms, the Dermatology Life Quality Index (DLQI) and the Patients' Health Questionnaire (PHQ). Results A total of 297 respondents completed the survey. The majority of them (52.5%) reported worsened clinical symptoms of psoriasis during the COVID-19 lockdown period. In total, 43.1% of responders reported significant depressive symptoms (PHQ-9 ≥ 10) and 23.6% reported impaired disease-related QoL (DLQI > 10). The strongest predictor of psoriasis symptoms worsening was the need for changes in psoriasis treatment, with an odds ratio (OR) of 2.73 (95% CI 1.37–5.44, p = 0.004) and decreased income (OR = 2.33, 95% CI 1.30–4.17, p = 0.004). The strongest predictor of impaired QoL was male sex (OR = 3.35, 95% CI 1.70–6.59, p < 0.001). Contribution of specific depressive symptoms was evident for both models. Conclusion Worsening of psoriasis symptoms during the COVID-19 lockdown was associated with decreased income, psoriasis treatment changes and depression symptoms. Impaired QoL was associated with male sex, symptom worsening and depression. Specific depression symptoms may have contributed to more symptom worsening and impaired QoL than the depressive symptomatology as a whole.